Progress in the Effect of Cations on the Gel Properties of Soy Protein and Its Fractions - Yuyang HUANG; Jiyuan LIU; Ying ZHU; Bingyu SUN; Linlin LIU; Mingshou LÜ; Xiuqing ZHU (Shipin gongye ke-ji)
Soy proteins are a popular alternative to animal proteins and contain all the essential amino acids. Their excellent gel properties make them useful in processing industries, including the production of tofu, soy yogurt, 3D food printing, and biological materials. Cation induction is a commonly used method to enhance the gel properties of soy proteins, with the type and concentration of cations influencing the structural properties of soy protein gels. This article explores the effects of different cations on soy protein gel formation and their fractions. It also summarizes the effects of cations on soy protein and its fractions in terms of aggregation and gelling. Finally, the article outlines the mechanism of cation-induced soy protein gelation, providing a valuable reference for the effective use of soy protein gel products.